Retraction notice to: ‘Literacy lessons learnt from parents after attending a seven-week Home-School Partnership Programme’, South African Journal of Childhood Education 6(1), a291 - AOSIS Publishing (South African Journal of Childhood Education, 2016)
Reason: The article ‘Literacy lessons learnt from parents after attending a seven-week Home School Partnership Programme' (DOI: http://dx.doi.org/10.4102/sajce.v6i1.291)’ published on 30 June 2016 in the South African Journal of Childhood Education has been retracted by agreement between the authors (Dawn Cozett and Janet Condy) and the journal’s Editor-in-Chief Elizabeth Henning because of duplicate publication. The initial article was published on 21 June 2016 in the South African Journal of Childhood Education (DOI: http://dx.doi.org/10.4102/sajce.v6i1.364). Duplicate publication was not the authors’ intention, but a mistake of the publisher. We deeply regret this mistake and apologise for any inconvenience to the authors and readers of the South African Journal of Childhood Education.